Парадигматичні відношення прикметників на семантичному рівні у художньому стилі - Данилович, Оксана Дмитрівна (Видавничий дім "Гельветика", 2023)
The article is dedicated to the investigation of paradigmatic relations of LSG of adjectives in the belle-lettres style. 22 LSG of adjectives were used in our investigation. The correlation analysis was used to investigate paradigmatic ties and their character. Paradigmatic ties with the highest correlation coefficients were distinguished. Due to correlation analysis paradigmatic ties were divided into strong, medium and weak ties according to their correlation coefficients. Strong paradigmatic ties and the frequency of usage of LSG of adjectives were analyzed. Common sematic areas of syntagmatic ties in comparison of strong paradigmatic ties of LSG of adjectives were defined. The object of the study is LSG of adjectives in the belle-lettres style. The subject of the study is paradigmatic ties on the semantic level. The goal is to distinguish and compare strong paradigmatic ties of adjectives. The topicality is caused by the necessity of distinguishing and analyzing paradigmatic ties as they have not been investigated yet. Conclusions. The analysis of frequency of usage of LSG of adjectives distinguished that LSG of adjectives with high and medium usage of frequency prevail except 2 LSG of adjectives with a low usage “Religion, race” and “Speed”. The investigation of strong paradigmatic ties turned out that LSG of adjectives “Religion, race” has the biggest number of paradigmatic ties with a low frequency of usage and a medium number of syntagmatic partners. Both LSG of adjectives “Traits of character” and “Emotional state, feelings” have the same big number of paradigmatic ties with an essential difference in frequency of usage and the number of syntagmatic ties. So it proves that LSG of adjectives correlate between themselves not only by common semantic areas but also by common semantics as additional signs.
Paradigmatic relations of adjectives on the semantic level in the belle-lettres style
Keywords: сполучуваність, прикметник, лексико-семантична група, парадигматичні зв’язки.